2017
DOI: 10.1128/cvi.00099-17
|View full text |Cite
|
Sign up to set email alerts
|

The Pneumococcal Serotype 15C Capsule Is Partially O-Acetylated and Allows for Limited Evasion of 23-Valent Pneumococcal Polysaccharide Vaccine-Elicited Anti-Serotype 15B Antibodies

Abstract: As a species, Streptococcus pneumoniae (the pneumococcus) utilizes a diverse array of capsular polysaccharides to evade the host. In contrast to large variations in sugar composition and linkage formation, O-acetylation is a subtle capsular modification that nonetheless has a large impact on capsular shielding and recognition of the capsule by vaccine-elicited antibodies. Serotype 15B, which is included in the 23-valent pneumococcal polysaccharide vaccine (PPV23), carries the putative O-acetyltransferase gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 63 publications
(74 reference statements)
1
21
0
Order By: Relevance
“…Serotypes were classified into vaccine serotypes, i.e., those included in PCV7 (serotypes 4, 6B, 9V, 14, 18C, 19F, and 23F), PCV13 (all PCV7 serotypes plus 1, 3, 5, 6A, 7F, and 19A, the later also referred to as addPCV13), PCV15 (all PCV13 serotypes plus 22F and 33F, the later also referred to as addPCV15), PCV20 (all PCV15 serotypes plus 8, 10A, 11A, 12F, and 15B, the later also referred to as addPCV20), and PPV23 (all PCV20 serotypes, except serotype 6A, plus serotypes 2, 9N, 17F and 20, the later also referred to as addPPV23), or as non-vaccine serotypes (NVTs). Given the high frequency of spontaneous switching between serotypes 15B and 15C, we decided to group isolates with these serotypes into a single group and to assume that PCV20 and PPV23 protect against both these serotypes [ 14 ]. Additionally, given the difficulties in phenotypically distinguishing isolates of serotypes 25A and 38, as well as isolates with serotypes 29 and 35B, these also grouped together into 25A/38 and 29/35B, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Serotypes were classified into vaccine serotypes, i.e., those included in PCV7 (serotypes 4, 6B, 9V, 14, 18C, 19F, and 23F), PCV13 (all PCV7 serotypes plus 1, 3, 5, 6A, 7F, and 19A, the later also referred to as addPCV13), PCV15 (all PCV13 serotypes plus 22F and 33F, the later also referred to as addPCV15), PCV20 (all PCV15 serotypes plus 8, 10A, 11A, 12F, and 15B, the later also referred to as addPCV20), and PPV23 (all PCV20 serotypes, except serotype 6A, plus serotypes 2, 9N, 17F and 20, the later also referred to as addPPV23), or as non-vaccine serotypes (NVTs). Given the high frequency of spontaneous switching between serotypes 15B and 15C, we decided to group isolates with these serotypes into a single group and to assume that PCV20 and PPV23 protect against both these serotypes [ 14 ]. Additionally, given the difficulties in phenotypically distinguishing isolates of serotypes 25A and 38, as well as isolates with serotypes 29 and 35B, these also grouped together into 25A/38 and 29/35B, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…89 In contrast, a recent investigation of the specificity of recognition of sera from a larger number of Pneumovax  immunized individuals, concluded on a rather slight difference of the opsonophagocytic activity of the induced sera in favor of type 15B in comparison to type 15C. 85 Interestingly, by use 5 of antibodies specifically targeting WciZ-mediated O-acetylation the same study revealed that the CPS from S. pneumoniae 15B and 15C were O-acetylated at the same location, albeit to a much lesser extent for the later (Fig. 9B).…”
Section: -85 30mentioning
confidence: 98%
“…It was found that wciZ coded by (TA) 7 or (TA) 9 wciZ retaining partial activity, whereas type 15C strains with (TA) 6 wciZ had barely detectable CPS O-acetylation levels. 85 In support to the assumption that the influence of O-acetylation on CPS biological properties is 15 polysaccharide-dependent, 75 it was suggested that CPS O-acetylation had little effect on the biological properties of CPS in the case of S. pneumoniae types 15B and 15C and allowed for only limited evasion of Pneumovax  -elicited anti-serotype 15B antibodies. 85 Whereas Pneumovax ® comprises type 15B, no member of pneumococci group 15 was included in Prevnar.…”
Section: -85 30mentioning
confidence: 99%
See 1 more Smart Citation
“…Capsule-specific antibodies are essential mediators of clearance and control during pneumococcal infections alongside other innate immune activators (ie, ficolin-2). [18][19][20] The increased microbial lung burden and susceptibility of asthmatic patients to infections suggest that further study of this population's immune response is warranted. M pneumoniae and S pneumoniae are convenient model organisms with which to explore the airway allergic immune response in mice.…”
mentioning
confidence: 99%